EFFECTS OF ACID AND ALKALINE TREATMENTS ON EFFICIENCY OF DIATOMACEOUS EARTH IN REMOVAL OF TETRACYCLINE IN AQUEOUS SOLUTION - Sarawut Sinpichai; Ratanaporn Yuangsawad; Duangkamol Na-Ranong (My University, 2023)
Contamination of tetracycline (TC) in environment may cause serious problems relating to increase of antibiotic resistance and development of new deceases. This paper focuses on TC removal by simple adsorption treatment and utilization of natural diatomaceous earth (NDE) as a cheap adsorbent. To improve efficiency of NDE, an impregnation method using acid (H2SO4) or base (KOH) was applied to modify NDE and influences of important activation parameters, concentration of reagent (Creagent), ratio of NDE weight and activating solution volume (NDE-to-Sol), temperature (Tact) and time (tact), on the efficiencies of the obtained acid and base activated diatomaceous earths (ADE and BDE) were investigated. Batch adsorption experiment was performed at the same condition to evaluate TC adsorption capacities at equilibrium (qe, TC) of NDE, ADE and BDE. It was found that acid activation negatively affected qe, TC and increases of CH2SO4, Tact and tact resulted in poorer ADE. In contrast, qe, TC was successfully enhanced through activation by KOH; Tact and tact played more significant roles on the enhancement, comparing with CKOH and NDE-to-Sol; impregnation at higher Tact and longer tact could improve efficiency of BDE and the best BDE (BDE-B) with the highest qe, TC (86.31 mg/g) was obtained at 3 M, 0.1 g/ml, 80 °C and 9 h.
Keywords: Tact; Base (topology); Adsorption and biosorption for pollutant removal